Nylon composite material, preparation method thereof and battery pack shell
By pretreating the reinforced filler with silane coupling agent in the battery case material and combining with the micro-foam injection molding process, nylon composite materials were prepared, which solved the shortcomings of existing materials in terms of lightweight, strength and flame retardant properties, and achieved both low density, high strength and high flame retardant properties.
Patent Information
- Application Number
- CN202411556567.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-25
AI Technical Summary
The existing battery pack shell materials still have great room for development in terms of lightweight, and it is difficult to have both low density, high strength and high flame retardant properties.
The reinforced filler is pretreated with silane coupling agent and mixed with semi-aromatic nylon, flame retardant, silane coupling agent, antioxidant and anti-UV aging agent to prepare nylon composite material through a micro-foam injection molding process.
The low density, excellent flame retardant properties and high tensile strength of nylon composite materials are achieved, achieving the purpose of lightweighting of the battery case.
Smart Images

Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and in particular to a nylon composite material and a preparation method thereof, and a battery pack shell. Background Art
[0002] The improvement of the cruising range of new energy vehicles is closely related to the lightweighting of vehicles. When the total weight of new energy vehicles is reduced by 10%, its cruising range can be increased by 5%~6%. At present, lightweight technology has become the core means of saving energy, reducing consumption and improving the cruising range of vehicles. The battery pack of new energy vehicles accounts for about 50% of the weight of the whole vehicle. The battery pack shell is the carrier of the power battery of new energy vehicles. It is used to protect the lithium battery from damage when it is hit or squeezed by the outside world. It accounts for about 10%~20% of the total weight of the battery pack and is the component with the highest weight besides the battery cell. Therefore, the lightweighting of the battery pack shell is particularly important for the weight reduction of the battery pack and new energy vehicles.
[0003] In traditional technologies, in order to achieve the goal of lightweighting the battery pack shell, commonly used lightweight materials include high-strength steel, aluminum alloy and sheet molded composite (SMC), etc. At present, the material of the battery pack shell is gradually developing from metal materials to low-density composite materials, but there is still a large space for lightweight development. Summary of the invention
[0004] Based on this, one or more embodiments of the present application provide a nylon composite material with low density, excellent flame retardant properties and tensile strength, a preparation method thereof, and a battery pack shell.
[0005] According to a first aspect of an embodiment of the present application, a method for preparing a nylon composite material is provided, comprising the following steps:
[0006] Pre-treating the reinforcing filler with a silane coupling agent to obtain a modified reinforcing filler;
[0007] The modified reinforcing filler, semi-aromatic nylon, flame retardant, silane coupling agent, antioxidant and anti-ultraviolet aging agent are mixed and granulated to obtain a mixture;
[0008] The mixture is subjected to micro-foaming injection molding treatment to obtain the nylon composite material.
[0009] In one embodiment, the amount of each raw material is as follows, by weight: 100 parts of semi-aromatic nylon, 10-50 parts of reinforcing filler, 5-20 parts of flame retardant, 0.5-2.5 parts of silane coupling agent, 0.5-2 parts of antioxidant, and 0.5-2 parts of anti-ultraviolet aging agent.
[0010] In one embodiment, the preparation method satisfies at least one of the following conditions:
[0011] (1) In the micro-foam injection molding process, the front section temperature is 240℃~280℃, the middle section temperature is 290℃~320℃, the rear section temperature is 300℃~330℃, the nozzle temperature is 300℃~330℃, and the mold temperature is 80℃~130℃;
[0012] (2) In the micro-foam injection molding process, the injection pressure is 80MPa~150MPa;
[0013] (3) In the micro-foam injection molding process, the foaming rate is 5%~15%.
[0014] In one embodiment, pre-treating the reinforcing filler with a silane coupling agent comprises the following steps:
[0015] Mixing the silane coupling agent with water to obtain a modified solution;
[0016] The modified solution and the reinforcing filler are stirred and mixed, and dried to obtain the modified reinforcing filler.
[0017] In one embodiment, the antioxidant includes a primary antioxidant and a secondary antioxidant;
[0018] The primary antioxidant includes one or more of a hindered phenol antioxidant and a hindered amine antioxidant, and the auxiliary antioxidant includes one or more of a phosphite antioxidant, an organic sulfide and a metal ion passivator.
[0019] In one embodiment, the flame retardant includes one or more of a halogen flame retardant, an antimony flame retardant, a phosphorus flame retardant, and a nitrogen flame retardant.
[0020] In one embodiment, the semi-aromatic nylon is selected from PA10T.
[0021] In one embodiment, the reinforcing filler includes one or more of glass fiber, mineral fiber, carbon fiber and whisker.
[0022] In one embodiment, the silane coupling agent includes one or more of KH550 and KH570.
[0023] In one embodiment, the anti-ultraviolet aging agent includes one or more of a light shielding agent, an ultraviolet absorber, a quencher and a free radical scavenger.
[0024] A nylon composite material is prepared by adopting the above-mentioned preparation method of the nylon composite material.
[0025] A battery pack shell, the raw materials for preparing the shell include the above-mentioned nylon composite material.
[0026] Compared with the traditional technology, this application has the following beneficial effects:
[0027] The present application adds inorganic reinforcing fillers to semi-aromatic nylon, whose mechanical strength is higher than that of semi-aromatic nylon, and can reduce the amount of raw materials while maintaining the mechanical strength, so that the prepared nylon composite material has a lower density while having both high strength and high flame retardant properties; further, the use of a physical micro-foaming injection molding process to prepare the nylon composite material can further reduce its density and achieve the purpose of lightweighting. DETAILED DESCRIPTION
[0028] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present application, etc. can be purchased from the market or can be prepared by existing methods.
[0030] Some embodiments of the present application provide a method for preparing a nylon composite material, comprising steps S10 to S30.
[0031] Step S10: pretreating the reinforcing filler with a silane coupling agent to obtain a modified reinforcing filler;
[0032] Step S20: mixing the modified reinforcing filler, semi-aromatic nylon, flame retardant, silane coupling agent, antioxidant and anti-ultraviolet aging agent, granulating to obtain a mixture;
[0033] Step S30: performing micro-foaming injection molding on the mixture to obtain a nylon composite material.
[0034] It should be noted that the mass fraction of the semi-aromatic nylon in step S10 is not limited to the specific value of "100 parts". When the mass fraction of the semi-aromatic nylon changes, the mass fractions of other components change proportionally.
[0035] In some embodiments, in step S10, pre-treating the reinforcing filler with a silane coupling agent includes steps S11 and S12.
[0036] Step S11: mixing a silane coupling agent with water to obtain a modified solution;
[0037] Step S12: stirring and mixing the modified solution and the reinforcing filler, and drying to obtain the modified reinforcing filler.
[0038] In some specific embodiments, the mass fraction of the silane coupling agent in the modified solution is 1% to 5%.
[0039] As an example, the mass fraction of the silane coupling agent in the modified solution may be, but is not limited to, specific values such as 1%, 2%, 3%, 4% or 5%.
[0040] In some specific embodiments, the drying temperature in step S12 is 80° C. to 120° C.
[0041] As an example, the drying temperature may be, but is not limited to, specific values such as 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C.
[0042] It can be understood that surface modification of the reinforcing filler using a silane coupling agent can effectively improve the wettability and compatibility of the reinforcing filler with the resin matrix.
[0043] In some embodiments, in step S20, the amounts of the raw materials used are as follows, by weight: 100 parts of semi-aromatic nylon, 10 to 50 parts of reinforcing filler, 5 to 20 parts of flame retardant, 0.5 to 2.5 parts of silane coupling agent, 0.5 to 2 parts of antioxidant and 0.5 to 2 parts of anti-ultraviolet aging agent.
[0044] In some of the embodiments, the granulation in step S20 may be performed by any method and instrument commonly used in the art, as long as the purpose of the present application can be achieved.
[0045] In some embodiments, in the micro-foam injection molding process in step S30, the front section temperature is 240°C~280°C, the middle section temperature is 290°C~320°C, the rear section temperature is 300°C~330°C, the nozzle temperature is 300°C~330°C, and the mold temperature is 80°C~130°C.
[0046] As an example, the temperature of the front section can be but not limited to 240°C, 245°C, 250°C, 255°C, 260°C, 265°C, 270°C, 275°C or 280°C; the temperature of the middle section can be but not limited to 290°C, 295°C, 300°C, 305°C, 310°C, 315°C or 320°C; the temperature of the rear section can be but not limited to 300°C, 305°C, 310°C, 3 The nozzle temperature may be, but is not limited to, specific values such as 300°C, 305°C, 310°C, 315°C, 320°C, 325°C or 330°C; the mold temperature may be, but is not limited to, specific values such as 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C or 130°C. It can be understood that the above-mentioned front section temperature, middle section temperature, rear section temperature, nozzle temperature and mold temperature can be independently selected from specific parameters within the optional range.
[0047] It should be noted that the front section temperature refers to the barrel temperature area close to the injection molding machine hopper side; in the front section area, the plastic particles begin to be heated and gradually softened, preparing for the subsequent melting and plasticizing process. The middle section temperature refers to the temperature of the middle part of the barrel; in the middle section area, the plastic particles are fully heated and begin to melt, forming a uniform melt. The rear section temperature refers to the barrel temperature area close to the injection molding machine nozzle side; in the rear section area, the plastic melt has been fully heated and plasticized, ready to enter the mold cavity for injection molding.
[0048] In some embodiments, in the micro-foam injection molding process in step S30, the injection pressure is 80 MPa to 150 MPa. As an example, the injection pressure can be, but is not limited to, specific values such as 80 MPa, 90 MPa, 100 MPa, 110 MPa, 120 MPa, 130 MPa, 140 MPa or 150 MPa.
[0049] In some embodiments, the gas used in the micro-foam injection molding process in step S30 is selected from nitrogen or carbon dioxide.
[0050] In some embodiments, the foaming rate of the micro-foam injection molding process in step S30 is 5% to 15%. As an example, the foaming rate of the micro-foam injection molding process can be, but is not limited to, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%.
[0051] In some specific examples, the foaming rate of the micro-foam injection molding process is 5%~10%.
[0052] The present application adopts a specific component ratio and combines it with a physical micro-foaming injection molding process to further reduce the density of the nylon composite material, thereby achieving lightweighting of the automobile.
[0053] In some embodiments, the antioxidant includes a primary antioxidant and a secondary antioxidant; the primary antioxidant includes one or more of hindered phenol antioxidants and hindered amine antioxidants, and the secondary antioxidant includes one or more of phosphite antioxidants, organic sulfides and metal ion passivators.
[0054] In some specific embodiments, the primary antioxidant is selected from antioxidant 1010.
[0055] In some embodiments, the secondary antioxidant is selected from dilauryl thiodipropionate (DLTP).
[0056] Understandably, the primary antioxidant and the secondary antioxidant are used together, and the secondary antioxidant can convert the primary antioxidant into a certain amount of active Decompose it so that it will no longer re-trigger the auto-oxidation reaction, and the auxiliary antioxidant can inhibit and delay the generation of free radicals during the initiation process; the two have a synergistic protective effect.
[0057] In some embodiments, the flame retardant includes one or more of a halogen flame retardant, an antimony flame retardant, a phosphorus flame retardant, and a nitrogen flame retardant.
[0058] In some specific embodiments, the flame retardant includes a halogen flame retardant and an antimony flame retardant. Optionally, the mass ratio of the halogen flame retardant to the antimony flame retardant is 3:1.
[0059] In some specific embodiments, the flame retardant includes a halogen flame retardant and a phosphorus flame retardant. Optionally, the mass ratio of the halogen flame retardant to the phosphorus flame retardant is 3:2. In the halogen-phosphorus composite system, the halogen flame retardant mainly produces a gas phase flame retardant effect, and the phosphorus flame retardant produces a solid phase flame retardant effect, and the two form a complete gas-solid phase flame retardant system.
[0060] In some specific embodiments, the flame retardant includes a nitrogen flame retardant and a phosphorus flame retardant. The nitrogen flame retardant can promote the carbonization of phosphorus compounds, and the carbon layer covers the surface of the combustible to isolate oxygen and improve the flame retardant effect.
[0061] In some of these embodiments, the semi-aromatic nylon is selected from PA10T.
[0062] Semi-aromatic nylon (PPA) is a special engineering plastic with high strength, high heat resistance and high fluidity, which can be used as the matrix of nylon composite materials. According to the structure, semi-aromatic nylon includes PA4T, PA6T, PA9T, PA10T, etc.
[0063] PA4T has the shortest aliphatic diamine chain length, resulting in the highest melting point of 380°C, the highest melt viscosity, the worst processability, the largest amide group molar ratio, and the highest water absorption rate of about 0.6%; PA6T and PA9T have intermediate processability and water absorption rate; PA10T has the longest aliphatic diamine chain length, resulting in the lowest melting point of 316°C, the lowest melt viscosity, the best processability, the smallest amide group molar ratio, and the lowest water absorption rate of about 0.17%; considering that the battery pack is molded by micro-foam injection molding process, the material needs to have a lower molding temperature and better molding fluidity, and the battery pack needs to have higher dimensional stability and the material needs to have lower water absorption rate, so this application selects PA10T as the base material.
[0064] In some embodiments, the reinforcing filler includes one or more of glass fibers, mineral fibers, carbon fibers, and whiskers.
[0065] Glass fiber is the most widely used reinforcing fiber, including E glass fiber, C glass fiber, D glass fiber, S glass fiber, AR glass fiber, NE glass fiber, high silica glass fiber, quartz glass fiber, etc. Among them, E glass fiber is the cheapest and most commonly used glass fiber material, and S glass fiber is the strongest glass fiber material. In terms of morphology, it can be divided into short glass fiber and long glass fiber. The length of short glass fiber is 0.2mm~3mm, and the aspect ratio is 15~50; the length of long glass fiber is 6mm~25mm, and the aspect ratio is 50~100; long glass fiber reinforced materials have better mechanical properties than short glass fiber reinforced materials, but the molding fluidity becomes worse, so this application gives priority to short glass fiber.
[0066] Mineral fiber is a fiber obtained from mineral rocks with a fibrous structure, including basalt fiber and asbestos fiber, etc. Its reinforcing effect is worse than that of glass fiber.
[0067] Carbon fiber refers to high-strength and high-modulus fiber with a carbon content of more than 90%. It has the advantages of low density, high specific strength and high specific modulus. It can be divided into T300, T600, T700, T800 and T1000 according to the tensile strength level.
[0068] Whiskers are micro-nanoscale short fibers grown from high-purity single crystals. They can be divided into two categories: organic whiskers and inorganic whiskers. Organic whiskers include cellulose whiskers, poly(butyl acrylate-styrene) whiskers, and poly(4-hydroxybenzyl ester) whiskers (PHB whiskers). Inorganic whiskers mainly include ceramic whiskers (such as SiC, potassium titanate, aluminum borate, etc.), inorganic salt whiskers (such as calcium sulfate, calcium carbonate, etc.) and metal whiskers (aluminum oxide, zinc oxide, etc.).
[0069] In some embodiments, the silane coupling agent includes one or more of KH550 and KH570.
[0070] It can be understood that the silane coupling agent can couple the semi-aromatic nylon and the reinforcing filler together to enhance the compatibility of the system; and the amount of the silane coupling agent can vary with the reinforcing filler.
[0071] In some embodiments, the anti-ultraviolet aging agent includes one or more of a light shielding agent, an ultraviolet absorber, a quencher, and a free radical scavenger.
[0072] In some specific embodiments, the light shielding agent includes one or more of carbon black, zinc oxide, and titanium dioxide.
[0073] In some specific embodiments, the ultraviolet light absorber includes one or more of a salicylate ultraviolet light absorber, a benzophenone ultraviolet light absorber, a benzotriazole ultraviolet light absorber, a substituted acrylonitrile ultraviolet light absorber, and a triazine ultraviolet light absorber.
[0074] In a specific example, the anti-ultraviolet aging agent is selected from UV-327.
[0075] The above-mentioned preparation method of the present application also has the advantages of simple process and wide source of raw materials.
[0076] A nylon composite material is prepared by adopting the above-mentioned preparation method of the nylon composite material.
[0077] The nylon composite material of the present application has low density and good strength and flame retardant properties.
[0078] A battery pack shell, the raw materials for preparing which include the above-mentioned nylon composite material.
[0079] The battery pack shell prepared using the nylon composite material of the present application has the advantages of light weight, etc., and can achieve the purpose of lightweighting the automobile.
[0080] The present application will be further described below in conjunction with specific examples and comparative examples, but they should not be construed as limiting the scope of protection of the present application. The raw materials involved in the following specific examples, unless otherwise specified, can all be sourced from commercial sources, the instruments used, unless otherwise specified, can all be sourced from commercial sources, and the processes involved, unless otherwise specified, are all conventionally selected by those skilled in the art.
[0081] The raw materials used in the examples and comparative examples of the present application include the following:
[0082] PA10T was purchased from Kingfa Technology Co., Ltd., the product model is Vicnyl;
[0083] E glass fiber (chopped) was purchased from Jushi Company, product model 560A;
[0084] S glass fiber (chopped) was purchased from Taishan Fiberglass Company, product model S-1HM;
[0085] Carbon fiber (chopped) was purchased from Toray, product model T300;
[0086] Bromotriazine was purchased from Shandong Xurui New Materials, product model SR-103;
[0087] Antimony trioxide was purchased from Shenzhen Ruihong Company, product model RH-03W101;
[0088] The silane coupling agent was purchased from Shandong Huachen Company, with the product model being KH550;
[0089] Antioxidant 1010 was purchased from Changzhou Xince Company, and the product model is Antioxidant 1010;
[0090] The antioxidant DLTP was purchased from Shandong Polymer Co., Ltd., with the product model number PW-922B;
[0091] The anti-ultraviolet aging agent UV-327 was purchased from Dongguan Shengbang Company, and the product model is UV-327.
[0092] Example 1
[0093] (1) Provide the following raw materials in parts by mass: 100 parts of PA10T, 50 parts of E glass fiber (chopped, length 3 mm, diameter 13 μm), 9 parts of bromotriazine, 3 parts of antimony trioxide, 1.5 parts of silane coupling agent KH550, 0.2 parts of antioxidant 1010, 0.5 parts of antioxidant DLTP and 0.3 parts of UV aging inhibitor UV-327.
[0094] (2) Dissolve 1.5 parts of silane coupling agent KH550 in water to prepare a modified solution with a mass percentage of 5%; add 50 parts of E glass fiber to the modified solution and stir thoroughly to ensure that the surface of all E glass fibers is evenly adhered to the hydrated silane coupling agent, then remove and put into an oven to dry at 100°C to obtain E glass fiber modified with silane coupling agent.
[0095] (3) Add the modified E glass fiber obtained in step (2) and the remaining raw materials in step (1) to PA10T, mix them evenly with a high-speed mixer, and granulate them with a twin-screw extruder to obtain a mixture.
[0096] (4) Physical micro-foaming injection molding process: First, carbon dioxide is passed through a supercritical fluid control system to generate a supercritical fluid, which is then injected into the homogenizing zone of the injection molding machine screw through the gas injection channel. Through the plasticizing and shearing of the screw, the mixture prepared in step (3) and the supercritical fluid are fully dissolved in the homogenizing zone to form a single-phase melt and maintained at a certain constant pressure. When the injection command of the injection molding machine is issued, the self-locking nozzle will open and inject the single-phase melt into the mold cavity, and the nylon composite material is obtained by injection molding.
[0097] Injection temperature: front section temperature is 280℃, middle section temperature is 310℃, rear section temperature is 330℃, nozzle temperature is 330℃, injection pressure is 100MPa, mold temperature is 100℃, and foaming rate is 5%.
[0098] Example 2
[0099] It is basically the same as Example 1, except that the raw materials of the nylon composite material are different.
[0100] (1) Provide the following raw materials in parts by mass: 100 parts of PA10T, 40 parts of S glass fiber (chopped, length 3 mm, diameter 13 μm), 9 parts of bromotriazine, 3 parts of antimony trioxide, 1.2 parts of silane coupling agent KH550, 0.2 parts of antioxidant 1010, 0.5 parts of antioxidant DLTP and 0.3 parts of UV aging inhibitor UV-327.
[0101] (2) Dissolve 1.5 parts of silane coupling agent KH550 in water to prepare a modified solution with a mass percentage of 5%; add 40 parts of S glass fiber to the modified solution and stir thoroughly to ensure that the surface of all S glass fibers is evenly adhered to the hydrated silane coupling agent, then remove and put into an oven to dry at 100°C to obtain S glass fiber modified with silane coupling agent.
[0102] (3) Add the modified S glass fiber obtained in step (2) and the remaining raw materials in step (1) to PA10T, mix them evenly with a high-speed mixer, and granulate them with a twin-screw extruder to obtain a mixture.
[0103] (4) Physical micro-foaming injection molding process: First, carbon dioxide is passed through a supercritical fluid control system to generate a supercritical fluid, which is then injected into the homogenizing zone of the injection molding machine screw through the gas injection channel. Through the plasticizing and shearing of the screw, the mixture prepared in step (3) and the supercritical fluid are fully dissolved in the homogenizing zone to form a single-phase melt and maintained at a certain constant pressure. When the injection command of the injection molding machine is issued, the self-locking nozzle will open and inject the single-phase melt into the mold cavity, and the nylon composite material is obtained by injection molding.
[0104] Injection temperature: front section temperature is 280℃, middle section temperature is 310℃, rear section temperature is 330℃, nozzle temperature is 330℃, injection pressure is 100MPa, mold temperature is 100℃, and foaming rate is 5%.
[0105] Example 3
[0106] It is basically the same as Example 1, except that the raw materials of the nylon composite material are different.
[0107] (1) Provide the following raw materials in parts by mass: 100 parts of PA10T, 30 parts of carbon fiber (chopped, length 3 mm, diameter 7 μm), 9 parts of bromotriazine, 3 parts of antimony trioxide, 0.9 parts of silane coupling agent KH550, 0.2 parts of antioxidant 1010, 0.5 parts of antioxidant DLTP and 0.3 parts of UV aging inhibitor UV-327.
[0108] (2) Dissolve 1.5 parts of silane coupling agent KH550 in water to prepare a modified solution with a mass percentage of 5%; add 40 parts of carbon fiber T300 to the modified solution and stir thoroughly to ensure that the surface of all carbon fiber T300 is evenly adhered to the hydrated silane coupling agent, then remove and put into an oven to dry at 100°C to obtain carbon fiber T300 modified with silane coupling agent.
[0109] (3) Add the modified carbon fiber obtained in step (2) and the remaining raw materials in step (1) to PA10T, mix them evenly with a high-speed mixer, and granulate them with a twin-screw extruder to obtain a mixture.
[0110] (4) Physical micro-foaming injection molding process: First, carbon dioxide is passed through a supercritical fluid control system to generate a supercritical fluid, which is then injected into the homogenizing zone of the injection molding machine screw through the gas injection channel. Through the plasticizing and shearing of the screw, the mixture prepared in step (3) and the supercritical fluid are fully dissolved in the homogenizing zone to form a single-phase melt and maintained at a certain constant pressure. When the injection command of the injection molding machine is issued, the self-locking nozzle will open and inject the single-phase melt into the mold cavity, and the nylon composite material is obtained by injection molding.
[0111] Injection temperature: front section temperature is 280℃, middle section temperature is 310℃, rear section temperature is 330℃, nozzle temperature is 330℃, injection pressure is 100MPa, mold temperature is 100℃, and foaming rate is 5%.
[0112] Example 4
[0113] It is basically the same as Example 1, except that the injection amount of the supercritical fluid in the micro-foam injection molding process is adjusted to achieve a foaming rate of 10%.
[0114] Injection temperature: front section temperature is 280℃, middle section temperature is 310℃, rear section temperature is 330℃, nozzle temperature is 330℃, injection pressure is 110MPa, and mold temperature is 100℃.
[0115] Example 5
[0116] It is basically the same as Example 1, except that the injection amount of the supercritical fluid in the micro-foam injection molding process is adjusted to achieve a foaming rate of 15%.
[0117] Injection temperature: front section temperature is 280℃, middle section temperature is 310℃, rear section temperature is 330℃, nozzle temperature is 330℃, injection pressure is 120MPa, and mold temperature is 100℃.
[0118] Comparative Example 1
[0119] The method is basically the same as Example 1, except that in step (4), ordinary injection molding process is used instead of micro-foaming injection molding process, that is, no supercritical fluid is injected, and the foaming rate is 0.
[0120] Injection temperature: front section temperature is 280℃, middle section temperature is 310℃, rear section temperature is 330℃, nozzle temperature is 330℃, injection pressure is 100MPa, and mold temperature is 100℃.
[0121] The components of the nylon composite materials and the parameters of the micro-foam injection molding process in the above Examples 1 to 5 and Comparative Example 1 are shown in Table 1.
[0122] Table 1
[0123]
[0124] The nylon composite materials prepared in the above embodiments and comparative examples, and the commercially available SMC polyester film plastics were subjected to performance tests, including density test, tensile strength test and flame retardant grade test. The specific test results are shown in Table 2.
[0125] The density test is carried out in accordance with the national standard GB / T 1033-2010; the tensile strength test is carried out in accordance with the national standard GB / T 1040-2006; the flame retardant grade is carried out in accordance with the standard UL-94.
[0126] Table 2
[0127]
[0128] It can be seen from Table 2 that, compared with commercially available SMC polyester film plastics, the nylon composite material prepared by the method of the present application significantly reduces the material density and achieves lightweight while having comparable tensile strength and flame retardant properties.
[0129] It can be seen from Example 1 and Comparative Example 1 that a large number of fine closed cells with an average diameter of 1 μm to 100 μm are formed inside the polymer material through the micro-foam injection molding process, which significantly reduces the density of the nylon composite material and has a significant lightweight effect.
[0130] It can be seen from Examples 1 to 3 that there is a close relationship between the strength of the reinforcing filler and the density of the nylon composite material. The higher the filler strength (carbon fiber>S glass fiber>E glass fiber), the less filler is required, and the more obvious the lightweight effect is.
[0131] It can be seen from Examples 1, 4, and 5 that the foaming ratio in the micro-foam injection molding process has an impact on the density and strength of the composite material. As the foaming ratio increases, the density of the composite material decreases almost linearly. When the foaming ratio reaches 10%, the density decreases significantly, while the strength is still comparable to the commercially available SMC polyester film plastic. However, when the foaming ratio reaches 15%, although the density is further reduced, the strength is much lower than the commercially available SMC polyester film plastic, making it difficult to apply to battery packs. This may be because when the foaming ratio increases to a certain extent, the pore effect of the material dominates, significantly reducing the strength of the body; therefore, an appropriate foaming ratio is the key to balancing weight loss and strength.
[0132] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0133] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A method for preparing a nylon composite material, characterized in that: The steps include: Pre-treating the reinforcing filler with a silane coupling agent to obtain a modified reinforcing filler; The modified reinforcing filler, semi-aromatic nylon, flame retardant, silane coupling agent, antioxidant and anti-ultraviolet aging agent are mixed and granulated to obtain a mixture; The mixture is subjected to micro-foaming injection molding treatment to obtain the nylon composite material.
2. The method for preparing the nylon composite material according to claim 1, characterized in that: The amount of each raw material used is as follows by weight: 100 parts of semi-aromatic nylon, 10-50 parts of reinforcing filler, 5-20 parts of flame retardant, 0.5-2.5 parts of silane coupling agent, 0.5-2 parts of antioxidant, and 0.5-2 parts of anti-ultraviolet aging agent.
3. The method for preparing the nylon composite material according to claim 1, characterized in that: The preparation method satisfies at least one of the following conditions: (1) In the micro-foam injection molding process, the front section temperature is 240℃~280℃, the middle section temperature is 290℃~320℃, the rear section temperature is 300℃~330℃, the nozzle temperature is 300℃~330℃, and the mold temperature is 80℃~130℃; (2) In the micro-foam injection molding process, the injection pressure is 80MPa~150MPa; (3) In the micro-foam injection molding process, the foaming rate is 5%~15%.
4. The method for preparing a nylon composite material according to claim 1, characterized in that: The pretreatment of reinforcing fillers with a silane coupling agent includes the following steps: Mixing the silane coupling agent with water to obtain a modified solution; The modified solution and the reinforcing filler are stirred and mixed, and dried to obtain the modified reinforcing filler.
5. The method for preparing a nylon composite material according to any one of claims 1 to 4, characterized in that: The antioxidants include primary antioxidants and auxiliary antioxidants; The primary antioxidant includes one or more of a hindered phenol antioxidant and a hindered amine antioxidant, and the auxiliary antioxidant includes one or more of a phosphite antioxidant, an organic sulfide and a metal ion passivator.
6. The method for preparing a nylon composite material according to any one of claims 1 to 4, characterized in that: The flame retardant includes one or more of a halogen flame retardant, an antimony flame retardant, a phosphorus flame retardant and a nitrogen flame retardant.
7. The method for preparing a nylon composite material according to any one of claims 1 to 4, characterized in that: The semi-aromatic nylon is selected from PA10T.
8. The method for preparing a nylon composite material according to any one of claims 1 to 4, characterized in that: The reinforcing filler includes one or more of glass fiber, mineral fiber, carbon fiber and whisker.
9. The method for preparing a nylon composite material according to any one of claims 1 to 4, characterized in that: The silane coupling agent includes one or more of KH550 and KH570.
10. The method for preparing a nylon composite material according to any one of claims 1 to 4, characterized in that: The anti-ultraviolet aging agent includes one or more of a light shielding agent, an ultraviolet absorber, a quencher and a free radical scavenger.
11. A nylon composite material, characterized in that: The nylon composite material is prepared by the preparation method of any one of claims 1 to 10.
12. A battery pack housing, characterized in that: The raw materials for preparing the same include the nylon composite material described in claim 11.